Investigation on luminescence properties and XANES of dysprosium ion doped borophosphate glasses. (July 2023) - Kiwsakunkran, N.; Chanthima, N.; Kim, H.J.; Kidkhunthod, P.; Kaewkhao, J.
Abstract: In this research, melt quenching was used to prepare Dy 3+ ion doped alkaline borophosphate glasses. According to the XANES measurement, Dy ions in glass show +3 oxidation state, identical to the standard Dy2 O3 powder. Glasses were measured for density ( ρ ), molar volume ( V m ), and refractive index ( n ). The absorption peaks, which are assigned to transitions from the ground state 6 H15/2 to higher energy levels of Dy 3+ ion in glass matrix. Four prominent emission bands were observed in luminescence spectra, which correspond to the 4 F9/2 → 6 HJ (J = 15/2, 13/2, 11/2, 9/2) transitions. The Judd-Ofelt (J-O) intensity parameters follow the trend as Ω2 >Ω6 >Ω4 of the PBLAGdDy1.0 . For the stimulated emission cross-section and branching ratio (>0.5), 4 F9/2 → 6 H13/2 transition was found to be higher than other transitions. Because the decay curves of glasses with different concentrations of Dy 3+ ion were found to be non-exponential, these glasses were calculated using the Inokuti-Hirayama (I-H) model. The obtained photoluminescence and decay times spectra primarily showed energy transfer effects from Gd 3+ to Dy 3+ ions and the calculated values of energy transfer efficiency ( η ) found that the values increased, which confirms energy transfer from Gd 3+ to Dy 3+ ions. From this study, the current glasses could be useful in the applications of solid-state lasers, LEDs, and scintillation materials. Highlights: P2 O5 +B2 O3 +Al2 O3 +Li2 O + Gd2 O3 +Dy2 O3 glasses have been prepared by melt quenching method. The highest emission intensity is 1.0 mol% of Dy 3+ ions. The energy transfer efficiency (η) found an increase with Dy2 O3 contents. The integral scintillation efficiency was found in 20% of the BGO crystal.